The neutrophil-lymphocyte ratio predicts all-cause and cardiovascular mortality among United States adults with COPD: results from NHANES 1999–2018 - Chen, Zhao; Li, Wenqiang; Tang, Yuanchun; Zhou, Peng; He, Qian; Deng, Zhiping (Frontiers in Medicine, 2024)
Background: Neutrophil-to-lymphocyte ratio (NLR) is considered a biomarker of systemic inflammation and immune activation. However, its relationship with the risk of mortality in patients with chronic obstructive pulmonary disease (COPD) remains unclear. This study aimed to investigate the association between NLR and the risk of all-cause and cardiovascular mortality in patients with COPD.Methods: Data were collected from the National Health and Nutrition Examination Survey (NHANES) from January 1999 to December 2018. The calculation method of NLR involves dividing the neutrophil count by the lymphocyte count in the total blood cell count. The optimal NLR threshold associated with survival outcomes was determined using the maximally selected rank statistics method (MSRSM). The relationship between NLR and the risk of all-cause mortality and cardiovascular mortality in COPD was investigated using a weighted multivariable Cox regression model. Additionally, restricted cubic spline (RCS) was employed to discuss the potential relationship between NLR patients in different groups and the risk of mortality.Results: In this study, 716 adults with COPD were included using the maximally selected rank statistics method, among whom 208 had higher NLR ( ≥ 2.56) and 508 had lower NLR (<2.56).During a median follow-up of 111.5 months, 162 COPD patients died from all causes, and 49 patients died from cardiovascular diseases. After adjusting for demographic, socioeconomic status, and lifestyle factors, the risk of all-cause mortality (HR=2.07, 95%CI: 1.46-2.94) and cardiovascular mortality (HR=3.03, 95%CI: 1.63-5.65) in patients with higher NLR was increased by 2-3 times compared to those with lower NLR. Kaplan-Meier analysis revealed significantly lower survival rates in patients with higher NLR for all-cause mortality and cardiovascular mortality (P<0.05). Restricted cubic spline analysis showed a linear correlation between NLR and the risk of all-cause mortality and cardiovascular mortality.NLR has a high value in independently predicting long-term all-cause and cardiovascular mortality risks in community-dwelling COPD patients. Therefore, NLR can serve as a cost-effective and widely available indicator for assessing the prognosis of COPD patients.